2020
DOI: 10.1002/acn3.50986
|View full text |Cite
|
Sign up to set email alerts
|

Insular and occipital changes in visual snow syndrome: a BOLD fMRI and MRS study

Abstract: Objective To investigate the pathophysiology of visual snow (VS), through a combined functional neuroimaging and magnetic resonance spectroscopy (1H‐MRS) approach. Methods We applied a functional MRI block‐design protocol studying the responses to a visual stimulation mimicking VS, in combination with 1H‐MRS over the right lingual gyrus, in 24 patients with VS compared to an equal number of age‐ and gender‐matched healthy controls. Results We found reduced BOLD responses to the visual stimulus with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(95 citation statements)
references
References 44 publications
2
93
0
Order By: Relevance
“…Several pathophysiologic hypotheses for the genesis of VSS have been proposed in the literature, 27 and hyperexcitation of primary and secondary visual cortices 28 31 seems to be one of the most plausible. In a condition where internal visual information is constantly being perceived, a state of increased cortical activation, justified by a form of processing overload, is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathophysiologic hypotheses for the genesis of VSS have been proposed in the literature, 27 and hyperexcitation of primary and secondary visual cortices 28 31 seems to be one of the most plausible. In a condition where internal visual information is constantly being perceived, a state of increased cortical activation, justified by a form of processing overload, is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported alterations in neurotransmission and fMRI signal strength during visual stimulation mimicking VS (Puledda et al, 2020). The authors observed reduced bilateral anterior insula BOLD responses to the visual stimulus with respect to baseline in VS patients compared to controls.…”
Section: Functional Alterationsmentioning
confidence: 94%
“…Increases in gray matter volume were seen in the right (R) lingual gyrus [p = 0.014, family-wise error (FWE) corrected, t-value = 4.61] in the patient group when compared to controls. noted in the FEF in patients with VS (Puledda et al, 2020). The FEF (but also the supramarginal gyrus) is involved not only in the control of eye movements but also in the control of visual awareness and visuospatial attention (Vernet et al, 2014;Quentin et al, 2015), and hyperconnectivity of this region to the AG might indicate abnormal attentional control.…”
Section: Functional Alterationsmentioning
confidence: 95%
See 2 more Smart Citations